2010
DOI: 10.1007/s10695-009-9375-x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacteria Lactobacillus rhamnosus influences the blood profile in rainbow trout Oncorhynchus mykiss (Walbaum)

Abstract: This paper reports the effect of feeding probiotic diets on blood profiles in rainbow trout. Two experiments were performed: in the first, fish of average weight 75 g were offered either a commercial feed or the same incorporated with 10(9) CFU g(-1) of lactic acid bacteria Lactobacillus rhamnosus for 30 days; in the second study performed for a similar duration, fish of average weight 126 g were offered formulated diets that either contained the same bacteria in heat-killed or freeze-dried form (nearly 10(11)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 35 publications
6
48
2
Order By: Relevance
“…To meet these goals, recently the simultaneous use of probiotics and prebiotics or Synbiotics has obtained special regards in aquaculture. Examinations of Synbiotics on fish have showed that they improve growth parameters by influence on gut microflora, digestion enzymes, appetite and immune system (Irianto and Austin 2002;Merrifield et al 2009;Panigrahi et al 2010;Montajami et al 2012;Nekoubin et al 2012). Nevertheless, rare information are available about the efficacy of Synbiotics on fish in particular sturgeons.…”
Section: Discussionmentioning
confidence: 99%
“…To meet these goals, recently the simultaneous use of probiotics and prebiotics or Synbiotics has obtained special regards in aquaculture. Examinations of Synbiotics on fish have showed that they improve growth parameters by influence on gut microflora, digestion enzymes, appetite and immune system (Irianto and Austin 2002;Merrifield et al 2009;Panigrahi et al 2010;Montajami et al 2012;Nekoubin et al 2012). Nevertheless, rare information are available about the efficacy of Synbiotics on fish in particular sturgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Total immunoglobulin was measured by the method of Panigrahi [19] and Bradford [20] . Briefly, the serum samples were diluted 100 times with 0.85% NaCl and the was employed to determining the total Immunoglobulin content, The bovine Plasma albumin (BSA) and reagents being sourced from Sigma (USA).…”
Section: Total Immunoglobulin Assaymentioning
confidence: 99%
“…In a study carried out by Panigrahi et al (2010), alteration in the blood profile was reported with an increase in plasma cholesterol, triglyceride and alkaline phosphatase activity level after feeding with probiotic strains. The increase in alkaline phosphate activity level is an indicator of good fish health condition (Tukmechi et al, 2007).…”
Section: Probiotics and Production Efficiency In Fishmentioning
confidence: 99%
“…There were alterations of metabolism and/or by the stimulation of host immunity. The strain used for this study enhanced fish growth, feed and nutrients utilization, fish chemical composition and muscular structure, besides fish resistance for pathogenic bacteria (Panigrahi et al, 2010). Another example where a probiotic strain was use to enhance the fish growth and health is in a research paper by Abd El-rhman et al (2009).…”
Section: Probiotics and Production Efficiency In Fishmentioning
confidence: 99%
See 1 more Smart Citation